2013
DOI: 10.1136/gutjnl-2012-304189
|View full text |Cite
|
Sign up to set email alerts
|

Visceral abdominal obesity measured by CT scan is associated with an increased risk of Barrett's oesophagus: a case-control study

Abstract: Objective Abdominal obesity has been associated with increased risk of Barrett’s oesophagus (BE) but the underlying mechanism is unclear. We examined the association between visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) and the risk of BE. Design A case-control study among eligible patients scheduled for elective oesophagastroduodenoscopy (EGD) and in a sample of patients eligible for screening colonoscopy recruited at the primary care clinic. All cases with definitive BE and a random s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 29 publications
3
87
0
3
Order By: Relevance
“…As discussed previously, obesity seems to promote the development of BO and OAC through reflux-dependent and -independent means, and epidemiologically the combination of obesity and reflux is a significantly greater risk than either alone or the additive effect [Duggan et al 2013;El-Serag et al 2014;Garcia et al 2014;Lagergren et al 1999]. This is reflected in further experimental data.…”
Section: The Role Of Adipokinessupporting
confidence: 54%
“…As discussed previously, obesity seems to promote the development of BO and OAC through reflux-dependent and -independent means, and epidemiologically the combination of obesity and reflux is a significantly greater risk than either alone or the additive effect [Duggan et al 2013;El-Serag et al 2014;Garcia et al 2014;Lagergren et al 1999]. This is reflected in further experimental data.…”
Section: The Role Of Adipokinessupporting
confidence: 54%
“…Increased cancer risk includes: long standing GERD (> 10 years), hiatal hernia > 3.0 cm, esophagitis, length of BE, history of BE with dysplasia, positive family history for esophageal and gastrointestinal cancer and obesity with an intraabdominal fat distribution [18][19][20][21][22]. RFA of NDBE should be conducted in specialized centers within clinical trials [23,24].…”
Section: Esophagogastroduodenoscopy Surveillance Recommendationmentioning
confidence: 99%
“…2,3 Several studies have suggested that abdominal obesity and visceral fat increased the risk of reflux esophagitis [4][5][6] or Barrett's esophagus. 7 Abdominal visceral adipose tissue not only mechanically disrupts the integrity of the gastroesophageal junction barrier and leads to increased esophageal reflux, 8 but also has a metabolic effect. 9 Abdominal visceral fat is metabolically active and increased inflammatory cytokines, insulin resistance, 9 and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%